OPTIMALISASI PERANAN FRONT OFFICE DALAM MELAYANI TAMU CHECK IN DAN CHECK OUT DI GRAND KARTINI HOTEL BUKITTINGGI - -, Yolveri, SH.MH (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The influences of rapid changes in the tourism and hospitality industry, particularlythe hospitality problem, require rapid reactions to hotels in the face of changes, cultural valuesshifts, social conditions and business globalization as well as economic growth on a micro andmacro scale.The hotel as one of the supporting tourism activities in the service aims to meetthe needs of the guests who come and want a place to stay (accommodation), eat, drink andother services contained in the hotel.As a company engaged in services, a hotel trying to realize the maximum profits, forit is required to prioritize the quality of service to its guests. If we provide good service, thenthe guests will also be a good promotional tool for the hotel. And ultimately the hotel canmake a profit with the arrival of new customers. To achieve these objectives then as a hotelemployee should be required to become a professional manpower. Basically the hotel is inneed of a professional workforce that has the expertise, skills and high discipline.To obtain professional staff, at this time has stood many tourism institutions thathave majors Hospitality majors, as well as many established professions courses that havemajors. To become a professional workforce, in addition to obtained from the science incollege, also obtained from On The Job Training (internship) in star hotels, thus can practicethe direct knowledge gained in college. Nevertheless, the services in the Front Office still needto be upgraded and there is still much to keep in mind, both from within the Front OfficeDepartment itself or in connection with the services of guests or with other departments in thehotel.Basically, guests will feel very happy and satisfied if they get the best service, wherethe service especially the Front Office is its own impression and the main for them so that themain factor to determine whether they will stay, extend the length of their stay at the hotel andof course the most expected one day they will certainly come back to stay at the hotel bybringing more members of the group.For that the first impression when first arrived at thehotel obtained from the front office in welcoming their arrival is a factor that determines thesatisfaction of guests in making decisions.Key Word : Hotel, Service,Employee and Facility.